Could emotion be measured by computer? The use of emwave biofeedback tool to investigate the effect of visual tafakur towards stress - Nur Yani, Che Hussin; Muhammad Nubli, Abdul Wahab; Syakira, Mohamad Alba (2019)
The objective of this study is to investigate the effect of visual tafakur towards stress using EmWave Biofeedback tool. Previous studies reported the effect on human emotion but there are limited study investigating the visual tafakur effect on stress. Visual activities such as seeing, watching and looking using sight sense that incorporate with remembering Allah can affect stress. Such activities were measured using EmWave Bioofeedback tool which measures heart rate variability of subjects. 30 study subjects involved were divided into treated group and controlled group. The result shows that visual tafakur could help in reducing stress thus improving mental health.